The Sustainability of Keeping Birds as Pets: Should Any Be Kept? - Shawn Peng; Donald M. Broom (Animals, 2021)
We describe a wide range of unethical and unsustainable practices inherent to the trading and keeping of pet birds. At present, biodiversity and wild bird populations are being greatly harmed and many individual birds have poor welfare. Wild-caught birds should not be sold to the public as pets, or to breeding establishments for several reasons, including because 75–90% of wild-caught birds die before the point of sale and taking birds from the wild has negative effects on biodiversity. The housing provided for pet birds should meet the needs of birds of that species and allow good welfare, for example there should be no small cages but aviaries with space for each bird to exercise adequately, and social birds should be kept in social groups. At present, inadequate housing of many pet birds results in stereotypies and other indicators of poor welfare in birds. Owners should have knowledge of how to provide good nutrition and minimize the risk of disease. Unless these changes are made, keeping birds as pets should not be permitted. New laws are needed to prohibit taking birds from the wild and ensure captive pet birds in conditions that do meet their needs.